Social anxiety and resilience among undergraduate medical students in Kolkata: A mixed-methods study - Saha, Sanjay Kumar; Pal, Partha Pratim; Barman, Neepamanjari; Basu, Mausumi; Pattanayak, Shalini; Kerketta, Prince (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Social anxiety disorder, or social phobia, involves an uncontrollable fear of social situations, exacerbating stress and hindering academic performance. Building resilience is crucial as it helps individuals cope with and recover from stress effectively. This study aimed to assess social anxiety and resilience among undergraduate medical students at a tertiary care institute in Kolkata and to identify any associated sociodemographic factors. Methods: A mixed-methods study was conducted from April to June 2022 among 200 undergraduate medical students of Phase-I of Bachelor of Medicine, Bachelor of Surgery. Quantitative data were collected via electronic method (Google Forms). Multinomial logistic regression was performed to examine relation between sociodemographic characteristics, social anxiety, and resilience. The qualitative component consisted of in-depth interviews with 12 purposively selected participants and was thematically analysed. Results: Most (80.0%) participants were aged between 17 and 20 years, and 63.7% were from urban residences. Social anxiety was prevalent in almost 78% of participants, while only 2.1% exhibited ‘high’ resilience. Students whose mothers had received primary education and less monthly pocket money had significantly higher odds of experiencing social anxiety. Qualitative findings revealed themes such as fear of judgment, avoidance of social situations, and impacts on academic performance, with coping mechanisms including seeking social support and practicing mindfulness. Conclusion: Most of the participants experienced social anxiety, with few displaying high resilience. These findings highlight the need for comprehensive mental health support systems within medical institutions.